LIABILITY OF THE NEW AND PREVIOUS OWNERS OF A VEHICLE FOR THE NON-PAYMENT OF ROAD TAXES - Beatrice-Ștefania NICULAE (Challenges of the Knowledge Society)
The present article aims to make a brief analysis of the applicable legal provisions, but also of the relevant judicial practice, regarding the application of the fine for non-payment of the necessary road taxes to the old owner by the competent authorities, despite the fact that the vehicle was already sold to the new owner. It is possible that the case presented will be considered as having a relatively simple solution, but in the context in which the new owner is in bad faith and does not fulfill its legal obligations and continues to accumulate fines for non-payment of the necessary road taxes, the previous owner will find himself in an unfair situation and which, at this point, could even be considered a legislative void.